Infecção natural e experimental de trypanosoma vivax em rebanhos leiteiros - Lopes, Francisco Canindé (Universidade Federal Rural do Semi-Árido, 2015)
Trypanosomiasis by Trypanossoma vivax is exotic disease of African origin increasingly common in Brazil, where reports of outbreaks in ruminants in the semiarid northeast are associated with high mortality, decrease in productive performance and economic losses. This study aimed to evaluate the clinical, epidemiological, production and quality of milk during natural infection by T. vivax in dairy cattle in western Rio Grande do Norte and verified the effect of infection on performance in experimentally infected dairy goats. This is the first Trypanosomiasis outbreak of T. vivax in dairy cattle herd occurred in properties located in the rural municipality of Mossoró-RN. Found 42 animals with trypomastigotes of T. vivax by smear of buffy coat in 467 cattle crossbred dairy breeds. High fever, anemia, decreased milk production, unilateral and bilateral tearing were the most frequent clinical signs. All cows with the parasite had sudden drop in milk production, and the physicochemical characteristics changed values, where the averages of lactose, fat, protein and density milk group with parasite was different from the healthy group. Influence of infection by T. vivax on the lactation curve behavior and the quality of milk in experimentally infected dairy goats was studied using 20 Saanen goats second lactation divided in two groups: the infected group, consisting of ten goats infected intravenously with approximately 1.25 x 105 trypomastigotes of T. vivax and ten animals were used as control. Milk production was measured every day for 152 days, by means of hand milking and weighing of the milk. To analyze the lactation curve parameters was used Wood model. Infected goats showed high parasitemy and hyperthermia addition to significant hematocrit reduction, serum total protein, albumin, glucose, cholesterol and increase in the urea concentration. Wood model showed that there was difference (P <0.05) to increase the rate values of milk production up to the peak, decline rate of milk production after the peak, milk production day at the peak, maximum milk production at peak and persistency of lactation in goats experimentally infected group compared goats in the control group, and physico-chemical characteristics of milk as fat, nonfat dry stratum, density and protein decreased significantly (P <0.05) in the group infected goats compared goats in the control group
Natural and experimental infection of Trypanosoma vivax in dairy herds
Keywords: Veterinary pathology; Milky cow; Dairy goat; Lactation curve; Milk composition; Patologia veterinária; Vaca leiteira; Cabra leiteira; Curva de lactação; Composição do leite; CIENCIAS AGRARIAS::MEDICINA VETERINARIA